Multi-proxy survey of open-air surface scatters in drylands: Archaeological and physico-chemical characterisation of fossilised dunes in North Gujarat (India). (29th April 2017) - Conesa, Francesc C.; Lobo, Agustin; Alcaina, Jonàs; Balbo, Andrea; Madella, Marco; Rajesh, S.V.; Ajithprasad, P.
Abstract: This research aims at improving our understanding of open-air archaeological surface scatters in drylands, their extension and the intensity of human activities during their occupation. To do so, the study of physico-chemical proxies is integrated to that of archaeological artefacts by means of systematic field survey combined with laboratory sedimentary analyses and a robust statistical approach. In most dry regions, archaeological survey has traditionally aimed at the collection of artefacts. When present, the study of physical and geochemical samples has been limited to excavated archaeological levels. In this work, we evaluate the archaeological significance of physico-chemical proxies from surface samples collected within and around four mid and late-Holocene surface scatters in North Gujarat, a semi-arid region located at the south-west margin of the Thar Desert in India. The four archaeological scatters are found on top of fossilised sand dunes. Archaeologically, they represent subsistence strategies based on hunting and gathering, agro-pastoralism, or a succession/mixture of the two. The four locations were systematically sampled across a linear transect. For each sampling unit, the archaeological materials were quantified and classified by means of a Linear Discriminant Analyses. Physio-chemical variables were ordinated in a PCA space and clustered through a Hierarchical Clustering. Results were displayed along the dune transect and integrated into a Correspondence Analysis. Significant differences are attested in the spatial distribution and content of Ca, P and grain size, allowing us to suggest a set of distinct cultural soilscapes that characterise the dunes of the study area: vertisols (agric horizons in interdunal lower slopes), aridisols (relict dune surfaces in the mid-slope), and anthrosols (top dune). The last show a strong correspondence with the presence of archaeological artefacts, and the different intensity of human footprint are discussed accordingly to potential past subsistence strategies and the intensity of human occupation.